Tata Kelola Keuangan Sederhana pada UMKM di Desa Jatisobo, Polokarto - Widi Hariyanti; Titiek Puji Astuti; Yunus Harjito; Nurul Herawati (Universitas Muria Kudus, 2022)
The process of managing and recording financial transactions requires special attention for financial managers. Every transaction activity needs to be recorded properly because it is information used by financial managers to prepare financial reports. The purpose of this community service activity is to increase knowledge in good financial recording practices to managers of UMKM in a simple way to improve their ability to manage and compile financial reports of their business units. The benefit of this community service activity is to train UMKM managers to be able to manage their business finances. The training was carried out because previously the UMKM managers in Jatisobo Village, Polokarto District, Sukoharjo Regency did not know and understand well how to manage and compile financial reports for their business units. This training activity can also encourage the development of UMKM that can support the improvement of the regional economy.